Climate risk adaptation by smallholder farmers: the roles of trees and agroforestry - Lasco, Rodel; Delfino, R.J.P.; Catacutan, D.C.; Simelton, Elisabeth; Wilson DM (Elsevier, 2014)
Smallholder farmers are vulnerable to environmental, climate and weather-related stress, including climate change. There is an increase in understanding of the benefits of agroforestry systems both at farm and landscape scales, and that incorporating trees on farms through agroforestry systems has emerged as having the potential to enhance the resilience of smallholders to current and future climate risks including future climate change. Drawing on global examples with a focus on African case studies, this paper demonstrates the versatile roles of trees and agroforestry in reducing smallholder's exposure to climate-related risks. It goes on to identify challenges in the promotion and adoption of agroforestry at the farm and landscape levels as a climate change adaptation strategy. The paper highlights areas for further research, policy and dissemination efforts, and identifies entry points for agroforestry adoption.